The Influence of Celebrity Endorsement Through Social Media Instagram on Purchase Intention at the Westin Resort Nusa Dua, Bali - Ni Made Suastini; I Putu Riyan Melvin; Prastha Adyatma; Ni Luh Gde Sri Sadjuni; Ni Luh Ketut Sri Sulistyawati (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
A guest's decision to stay is an important factor in the hospitality industry, and a decrease in the decision to stay can have an impact on room occupancy rates. Potential guests will consider various factors before deciding to make a purchase, and purchase intention will arise before they make a decision. One of the factors that can influence purchase intention is celebrity endorsement, which is utilizing celebrity figures. This study aims to determine how celebrity endorsement affects room purchase interest through Instagram social media at The Westin Resort Nusa Dua, Bali. The population of this study are Instagram social media users with the criteria, namely people who have an Instagram social media account and have seen The Westin Resort Nusa Dua, Bali using celebrity endorsement on Instagram social media. The sample size used in this study was 100 respondents. The questionnaire was distributed online via google form. The data analysis techniques used are classical assumption test, multiple linier regression test, t-test, F-test and coefficient of determination test. The results stated that there is a significant influence partially or simultaneously (together) between visibility, credibility, attraction and power owned by celebrity endorsement on room purchase interest through Instagram social media at The Westin Resort Nusa Dua, Bali. Overall, celebrity endorsement has a contribution to influence purchase intention by 52% in the moderate / moderate category, while the remaining 48% is influenced by other factors not examined in this study, namely online customer review and price.